2007
DOI: 10.1007/s10048-007-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-at-onset linkage analysis in Caribbean Hispanics with familial late-onset Alzheimer’s disease

Abstract: The aim of the study was to identify chromosomal regions containing putative genetic variants influencing age-at-onset in familial late-onset Alzheimer's disease. Data from a genome-wide scan that included genotyping of APOE was analyzed in 1,161 individuals from 209 families of Caribbean Hispanic ancestry with a mean age-at-onset of 73.3 years multiply affected by late-onset Alzheimer's disease. Two-point and multipoint analyses were conducted using variance component methods from 376 microsatellite markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
4
26
1
Order By: Relevance
“…This locus is a considerable distance (~33 cM) from the PSEN1 locus at 14q24. Suggestive linkage (Two-point LOD = 2.60) has been reported at 14q32 in an age-at-onset linkage analysis in Hispanic LOAD families [28]. The 1-LOD limit identified a region 0.78 Mbp in length containing C14orf177 and Mir_320, both of which have some support for involvement in dementia-related disease and processes.…”
Section: Discussionmentioning
confidence: 88%
“…This locus is a considerable distance (~33 cM) from the PSEN1 locus at 14q24. Suggestive linkage (Two-point LOD = 2.60) has been reported at 14q32 in an age-at-onset linkage analysis in Hispanic LOAD families [28]. The 1-LOD limit identified a region 0.78 Mbp in length containing C14orf177 and Mir_320, both of which have some support for involvement in dementia-related disease and processes.…”
Section: Discussionmentioning
confidence: 88%
“…The Collaborative Aging and Memory Project (CAMP) subjects are from the Amish communities of central Ohio and northern Indiana910. The Columbia University (CU) subjects are a Hispanic cohort described in detail elsewhere11. The Framingham Heart Study (FHS) is a single-site, community-based, ongoing cohort study described elsewhere1214.…”
Section: Methodsmentioning
confidence: 99%
“…14 Subsequent genome-wide linkage scans examining AAO in AD patients and unaffected family members (using age at study entry) found suggestive evidence of linkage on chromosome 19 to APOE (LOD = 3.28), 15 which was confirmed in later studies. 16 Multiple studies identified other suggestive linkage signals on chromosomes 4q, 8q, 16 1q, 6p, 17 7q, 15, and 19p 18 in Caucasian families, and chromosomes 5q, 7q, 14q, and 17q 19 in Caribbean Hispanics, though the specific loci driving these linkage signals remain unknown. More recently, an AAO GWAS in 2,222 Caucasian AD cases confirmed association at APOE , and also found strong evidence of association ( P =4.95×10 −7 ) on chromosome 4q31.3 in the gene DCHS2 .…”
Section: Introductionmentioning
confidence: 99%